Pengembangan Strategi Membangun Critical Thinking Melalui Pembelajaran Ekonomi Berbasis Konstruktivistik - Sakti, Norida Canda; Soesatyo, Yoyok; Surjanti, Jun; Fitrayati, Dhiah; Indah Nurlaili, Eka (Jurnal Pendidikan Ekonomi Undiksha, 2023)
21st century learning requires teachers to be able to create students who are knowledgeable, pious, and have character to be ready to face various educational challenges in the industrial revolution era. Economics teachers as an integral part of other subject teachers have a sense of professional responsibility and moral responsibility in preparing the nation's young generation. The analysis of students often has difficulty understanding macro and micro economic concepts that have not been answered by teachers in learning. So we need smart solutions to overcome them through changing the mindset of teachers in facing the challenges of teaching to be creative and willing to be good facilitators for students. The fusion of information technology applications in society needs to be revitalized in economic learning that is more effective, efficient and efficacy through strengthening economics teachers. Based on the urgency and conceptual ideas, the researcher intends to provide training for economics teachers in East Java on constructivist learning in economics learning to be able to improve students' critical thinking. This research was carried out using a participatory approach through the participation of teachers in seminar activities and continued with practical activities for training in constructivistic economic learning models and methods. The goal is to build critical thinking towards 21st century economic learning which is prepared independently by economics teachers. The results of the study indicate that the activities of developing constructivist-based economic learning models and methods have been proven to improve teacher understanding and skills as a form of developing strategies to build critical thinking.